Determinants of Migration to Accrual Accounting For the Central and Devolved Governments in Kenya - Ngahu, Solomon; Waweru, Cecilia Ndunge (Disclosure: Journal of Accounting and Finance, 2025)
Kenya’s public sector accounting is grappling with ongoing challenges that undermine fiscal transparency and accountability at both the national and county levels. Specifically, there are issues with accounting practices, such as unverified expenditures, missing financial records, and inconsistencies in financial reporting. The current paper assessed the determinants of migration to accrual accounting for the central and devolved Governments in Kenya. The specific objectives included; establishing the effect of the adequacy of budgetary resources and internal financial controls on migration to accrual accounting for the central and devolved Governments in Kenya. The study was grounded on positive accounting theory. It adopted a desk research approach and utilized a descriptive research design. This design was suitable for synthesizing the existing information published in peer-reviewed journals and reports. Purposive sampling guided journal selection. As a literature review, it relied on secondary information from studies related to accrual accounting. Data was analyzed qualitatively in line with the research problem and objectives. Findings from the analyzed empirical studies show that Kenya’s migration to accrual accounting in both central and devolved governments is determined by the adequacy of financial resources and the effectiveness of internal financial controls. It can concluded that the effective shift to accrual basis accounting in the public sector of Kenya depends on adequate allocation of financial resources and effective control systems. It is recommended that central and devolved governments prioritize funding to support personnel development and system enhancements essential for accrual basis accounting.